Longitudinal Human Milk miRNA Composition over the First 3 mo of Lactation in a Cohort of Healthy Mothers Delivering Term Infants. Issue 1 (11th September 2021) - Raymond, Frederic; Lefebvre, Gregory; Texari, Lorane; Pruvost, Solenn; Metairon, Sylviane; Cottenet, Geoffrey; Zollinger, Alix; Mateescu, Bogdan; Billeaud, Claude; Picaud, Jean-Charles; Silva-Zolezzi, Irma; Descombes, Patrick; et al.
ABSTRACT: Background: MicroRNAs (miRNAs) are small noncoding RNAs involved in posttranscriptional regulation. miRNAs can be secreted and found in many body fluids, and although they are particularly abundant in breastmilk, their functions remain elusive. Human milk (HM) miRNAs start to raise considerable interest, but a comprehensive understanding of the repertoire and expression profiles along lactation has not been well characterized. Objectives: This study aimed to characterize the longitudinal profile of HM miRNA between the second week and third month postpartum. Methods: We used a new sensitive technology to measure HM miRNAs in a cohort of 44 French mothers [mean ± SD age: 31 ± 3.5; BMI (in kg/m 2 ) 21.8 ± 2.3] who delivered at term and provided HM samples at 3 time points (17 ± 3 d, 60 ± 3 d, and 90 ± 3 d) during follow-up visits. Results: We detected 685 miRNAs, of which 35 showed a high and stable expression along the lactation period analyzed. We also described for the first time a set of 11 miRNAs with a dynamic expression profile. To gain insight into the potential functional relevance of this set of miRNAs, we selected miR-3126 and miR-3184 to treat undifferentiated Caco-2 human intestinal cells and then assessed differentially expressed genes and modulation of related biological pathways. Conclusions: Overall, our study provides new insights into HM miRNA composition and, to our knowledge, the first description of its longitudinal dynamics in mothers who delivered at term. Our in vitro results obtained in undifferentiated Caco-2 human intestinal cells transfected with HM miRNAs also provide further support to the hypothesized mother-to-neonate signaling role of HM miRNAs. This trial was registered at clinicaltrials.gov as NCT01894893.